2004
DOI: 10.1017/s1355617704104050
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume and retention in Alzheimer's disease

Abstract: This study tested the hypothesis that the hippocampus has a relatively specific role in retaining information over delays. Thirty-seven subjects with probable Alzheimer's disease were evaluated with a verbal memory task and structural MRI. Cortical gray matter but not hippocampal volume predicted immediate free recall. In contrast, hippocampal volume was the best predictor of how well information was retained over a delay, even after controlling for levels of immediate recall. Results suggest that the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 24 publications
13
47
1
4
Order By: Relevance
“…They agree with several earlier studies showing correlations between memory related cognitive measures and hippocampus [42] and amygdala [4,35,37] volume. In agreement with earlier studies [27,28], we found significant correlations of hippocampus volumes with delayed free recall, but not with immediate memory of a word list, supporting the specific role of hippocampus in the consolidation rather than encoding of new material [48]. Interestingly, however, not only delayed, but also immediate logical memory was correlated with hippocampal and amygdala volumes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They agree with several earlier studies showing correlations between memory related cognitive measures and hippocampus [42] and amygdala [4,35,37] volume. In agreement with earlier studies [27,28], we found significant correlations of hippocampus volumes with delayed free recall, but not with immediate memory of a word list, supporting the specific role of hippocampus in the consolidation rather than encoding of new material [48]. Interestingly, however, not only delayed, but also immediate logical memory was correlated with hippocampal and amygdala volumes.…”
Section: Discussionsupporting
confidence: 91%
“…Different to fixed effects models, mixed effects models allow drawing inference not only on the particular set of centres and raters involved, but on a whole population of centres and raters [49]. Earlier studies have used multicentre data as well, but either did not consider centre effects at all [28] or used a fixed effects model that does not allow for variation of effects between centres [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterações em outras funções cognitivas, como atenção, organização e memória de trabalho, afetam a forma como a nova informação será armazenada e posteriormente resgatada (Kramer et al, 2004). A maneira como essa nova informação será memorizada é mediada por regiões frontais, outras estruturas corticais que não o hipocampo, e também estruturas subcorticais (Stuss e Alexander, 2000;Mungas et al, 2001).…”
Section: Alterações De Memória Em Idosos Deprimidosunclassified
“…Correlação positiva entre memória e hipocampo foi verificada em exames de RM em pacientes neurológicos, como pacientes com DA Barber et al, 2001;Bottino et al, 2002;Kramer et al, 2004), e alguns estudos em sujeitos com comprometimento cognitivo leve (CCL) (Soininen et al, 1994;Jack et al, 2000;Bottino et al, 2002). No entanto, em estudo realizado por Duarte et al (2006), não foi encontrada nenhuma correlação nessa população.…”
Section: Estudos De Correlação Entre Estruturas Cerebrais E Desempenhunclassified